2019
DOI: 10.3390/rs11141679
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Hatch Filter Algorithm towards Sub-Meter Positioning Using only Android Raw GNSS Measurements without External Augmentation Corrections

Abstract: In May 2016, the availability of GNSS raw measurements on smart devices was announced by Google with the release of Android 7. It means that developers can access carrier-phase and pseudorange measurements and decode navigation messages for the first time from mass-market Android-devices. In this paper, an improved Hatch filter algorithm, i.e., Three-Thresholds and Single-Difference Hatch filter (TT-SD Hatch filter), is proposed for sub-meter single point positioning with raw GNSS measurements on Android devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…It should be noted, however, that a single satellite is capable of transmitting several signals on multiple frequencies at the same time, which considerably increases the number of pseudorange measurements that can be used by the receiver. This is why multi-GNSS receivers are now widely used in car navigation systems, other mobile applications, smartphones and sports [3][4][5][6][7][8], as well as even including modern dual-frequency solutions [9][10][11][12]. Their very rapid development, associated with increasing the positioning accuracy, particularly in urbanised areas, results primarily from the rapidly increasing number of satellites of systems under construction [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that a single satellite is capable of transmitting several signals on multiple frequencies at the same time, which considerably increases the number of pseudorange measurements that can be used by the receiver. This is why multi-GNSS receivers are now widely used in car navigation systems, other mobile applications, smartphones and sports [3][4][5][6][7][8], as well as even including modern dual-frequency solutions [9][10][11][12]. Their very rapid development, associated with increasing the positioning accuracy, particularly in urbanised areas, results primarily from the rapidly increasing number of satellites of systems under construction [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, forming a new type of GNSS observation based on integrating carrier phase observation and pseudorange is critical for GNSS (Global Navigation Satellite System) due to the ambiguity of the carrier phase and the high noise of the pseudorange [10]. The technology can absorb the advantages of the typical GNSS measurements, without ambiguity and high precision, and thereby forming a new pseudorange to aid cycle slip detection and repair [11], fixing ambiguity [12] and improving positioning accuracy [13]. Hatch [7] firstly designed a smoother on the basis that the variation between the two observations is equal within a period, with two main issues: (i) how to determine the smoothed pseudorange of first epoch and the smoothing time, and (ii) that it neglects the error sources, such as ionospheric variations and multipath at the period [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [14] comprehensively used satellite elevation angle, external augmentation information, and the distance change from the user to the base station to calculate the width of the smoothing window for a ground-based augmentation system (GBAS). Geng et al [15] proposed the Three-Thresholds and Single-Difference (TT-SD) Hatch filter to achieve sub-meter positioning with Android devices. Zhou et al [16] suggested using the Doppler phase difference observations rather than the carrier-phase observations to estimate the window width in kinematic positioning.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the width of the sliding ionospheric variation fitting window is long, and a 20-minute initialization time is required in realtime positioning to achieve the desired accuracy, which is unbearable for train positioning. Besides, this study used the ordinary least square method for parameter estimation, which makes it challenging to keep continuous positioning at the desired accuracy when the data quality is poor [15].…”
Section: Introductionmentioning
confidence: 99%